Analisis Serta Rekondisi Sistem Kemudi dan Sistem Suspensi Pada Minibus Isuzu Elf Tahun 1995 - Pramono, Bimo Suryo; Saleh, Moh. (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The purpose of this thesis is to find defects that occurred on a system of the helm and isuzu elf minibus suspension system, to repair, and to find out how well the system would serve after repaired.The process of the steering wheel and rekondisi suspension system minibus isuzu elf started by identifying damage to components.This is achieved by check the, the physical condition, performance, and measurement of components.After that, improvements in the wheel and suspension system minibus isuzu elf done by replacing or repairing damaged components, there is no complete components.Then penyetelan and testing done.The damage to the identification system covering damage on springs and shock an absorber spiral and mistakes of some components including myrrh, bolt, and rubber with a bushing.The identification damage to suspension system covering damage to link ball joint in drag, relay rod, tie rod, and tie rod end. Improvements in steering includes replacement of damaged all the components.The results show that testing rekondisi system steering and suspension minibus isuzu elf this back to function properly.